The Study of Market Structure and Competitive Behavior of Ready-to-Drink Tea Market in Thailand - Preedakorn, Panarach; Wattanachewanopakorn, Wanida (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2025)
This paper’s objective is to study the structure and behavior of the ready-to-drink tea market in Thailand and provide recommendations to promote competition and sustainable growth within the industry. The study begins with an analysis of the market context, including measuring market concentration and examining market behavior through an in-depth investigation of marketing data from ready-to-drink tea producers. It also analyzes barriers to market entry and assesses product substitutability and price elasticity of demand within the market. The study used secondary data from Thailand's ready-to-drink tea market and observed market price data within the studied period. Market structure analysis was conducted using market concentration measurement. The findings clearly indicate that the structure of the ready-to-drink tea market in Thailand resembles an oligopoly, where a few sellers hold significant market power. Market behavior is characterized by both direct and indirect price strategies, along with various promotional tactics. Ultimately, the study offers recommendations to develop the ready-to-drink tea market under a competitive context and to ensure the long-term sustainability of Thailand’s ready-to-drink tea industry. These include opening opportunities for new producers to enter the market to reduce the dominance of existing players, encouraging research and development of new ready-to-drink tea products that align more closely with the preferences of niche consumer groups, and promoting the development of a domestic supply chain for ready-to-drink tea to maximize economic benefits.